Populus ciliata Ã— Maximowiczii : Preliminary Report on a Potential Hybrid for Mid West Himalayan Zone - Khurana, D. K.; Thakur, Sanjeev (Indian Forester, 1995)
A systematic study on the crossability pattern and the culture method to be adopted for crossing Populus ciliata was conducted. The results showed grafting to be the most suitable method for greenhouse crossing of P. ciliata. It was easily crossable with Tacamahacan poplar. The progeny of P. ciliata Ã— maximowiczii could be successfully raised, and its hybrids have performed better than the parents in the initial growth trails within potential of being cultivated in the mid-West Himalayan zone.